Oral Immunization with a Multivalent Epitope-Based Vaccine, Based on NAP, Urease, HSP60, and HpaA, Provides Therapeutic Effect on H. pylori Infection in Mongolian gerbils - Guo, Le; Yang, Hua; Tang, Feng; Yin, Runting; Liu, Hongpeng; Gong, Xiaojuan; Wei, Jun; Zhang, Ying; Xu, Guangxian; Liu, Kunmei (Frontiers in Cellular and Infection Microbiology, 2017)
Epitope-based vaccine is a promising strategy for therapeutic vaccination against Helicobacter pylori (H. pylori) infection. A multivalent subunit vaccine containing various antigens from H. pylori is superior to a univalent subunit vaccine. However, whether a multivalent epitope-based vaccine is superior to a univalent epitope-based vaccine in therapeutic vaccination against H. pylori, remains unclear. In this study, a multivalent epitope-based vaccine named CWAE against H. pylori urease, neutrophil-activating protein (NAP), heat shock protein 60 (HSP60) and H. pylori adhesin A (HpaA) was constructed based on mucosal adjuvant cholera toxin B subunit (CTB), Th1-type adjuvant NAP, multiple copies of selected B and Th cell epitopes (UreA27-53, UreA183-203, HpaA132-141 and HSP60189-203), and also the epitope-rich regions of urease B subunit (UreB158-251 and UreB321-385) predicted by bioinformatics. Immunological properties of CWAE vaccine were characterized in BALB/c mice model. Its therapeutic effect was evaluated in H. pylori-infected Mongolian gerbil model by comparing with a univalent epitope-based vaccine CTB-UE against H. pylori urease that was constructed in our previous studies. Both CWAE and CTB-UE could induce similar levels of specific antibodies against H. pylori urease, and had similar inhibition effect of H. pylori urease activity. However, only CWAE could induce high levels of specific antibodies to NAP, HSP60, HpaA, and also the synthetic peptides epitopes (UreB158-172, UreB181-195, UreB211-225, UreB349-363, HpaA132-141 and HSP60189-203). In addition, oral therapeutic immunization with CWAE significantly reduced the number of H. pylori colonies in the stomach of Mongolian gerbils, compared with oral immunization using CTB-UE or H. pylori urease. The protection of CWAE was associated with higher levels of mixed CD4+ T cell (Th cell) response, IgG and secretory IgA (sIgA) antibodies to H. pylori. These results indicate that a multivalent epitope-based vaccine including Th and B cell epitopes from various H. pylori antigens could be a promising candidate against H. pylori infection.